Sex-, age-, and time-specific visual communication in brown bears - Penteriani, Vincenzo; Etchart, Léa; González-Bernardo, Enrique; Hartasánchez, Alfonso; Falcinelli, Daniele; Ruiz-Villar, Héctor; Morales-González, Ana; Delgado, María del Mar (Journal of Mammalogy, 2023)
Intraspecific communication in mammals is well-documented but generally restricted to chemical and acoustic signaling. However, other overlooked channels, such as visual signaling, may be used to communicate among conspecifics. Here, by using experimental manipulations together with camera traps on 13 brown bear (Ursus arctos) rubbing trees in the Cantabrian Mountains (northwestern Spain), we document detailed temporal patterns and behavioral aspects of a recently discovered novel communication channel for this species, visual signaling through the trunk debarking of focal trees. Video footage showed that visual marking is a sex-, age-, and time-specific means of communication in brown bears, being performed exclusively by adult males during the mating season (mainly April–June in the study area). Trunk debarking was always associated with chemical marking and was never an isolated behavior, suggesting that visual and chemical signals might be complementary. Visual and chemical marks may provide different information; for example, visual marks could be an indicator of individual size and, thus, the dominance status of adult males looking for mating opportunities. This is the first time that evidence is provided showing that visual signaling in a large carnivore is exclusive to a specific class of individuals (adult males) and linked to reproductive needs only. Bear visual signaling not only represents an advance in our comprehension of animal communication but may also serve to easily locate the mating areas of mammals, which are crucial for large carnivore species, such as the brown bear, that frequently need specific and urgent plans for conservation and management. During this work VP, EG-B, HR-V, and AM-G were supported by the I+D+i Project PID2020-114181GB-I00 financed by the Spanish Ministry of Science and Innovation, the Agencia Estatal de Investigación (AEI), and the Fondo Europeo de Desarrollo Regional (FEDER, EU). Juan Diaz García and David Cañedo (guards of the Bear Patrol—Patrulla Oso—of the ...